A Mobile Application Development for Monitoring Cash Transfer Program for MSMEs in Indonesia - Dita Pramesti; M. Rizal Bimantoro; Fitria Dewi Wulandari; Pradita Cahyani (School of Industrial and System Engineering, Telkom University, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in improving Indonesia’s economicgrowth that has been slowing down during the Covid-19 pandemic, an outbreak that significantly affectedthe national economy. MSMEs contribute 60.51% to Gross Domestic Product (GDP) of Indonesia andabsorb 96.29% of Indonesia’s workforce. In order to boost national economic recovery and growth, thegovernment is stimulating the growth in MSMEs by providing Bantuan Langsung Tunai (BLT) or CashTransfers for MSMEs. In practice, however, there are various problems in relation to the distribution of CashTransfers, such as illegal fees, corruption, misappropriation of funds, and mistargeting. In this paper, wepropose a mobile application design that can be a solution to all those problems. The application is designedto provide easy access for users to submit proposals and track the progress, with the result that the cash isdelivered efficiently and quickly to intended beneficiaries. This is an effort to promote openness andtransparency in public administration and also to prevent corruption that can occur in delivery of cash. Thisapplication, namely “Sumbangsih”, applies a prototype method as the System Development Life Cycle(SDLC), which consists of six phases: planning, analysis, design, implementation, testing, and maintenance.In the final phase, after the application is created, testing is carried out using User Acceptance Test (UAT)to verify that every function of the application is working exactly as required.